Factors Affecting Financial Statement Fraud in Food & Beverage Sub-Sector Companies: - - Pratiwi, Wiwik Pratiwi; Adelia Permata Putri; Nuryadin (Jurnal Riset Akuntansi dan Auditing, 2024)
This study aims to test whether there is an effect of the nature of the industry, financial targets, and financial stability on financial statement fraud. The population used in this study are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2019–2021. Sampling was done using the purposive sampling method, so 11 companies were obtained that met the research criteria and 33 observers. The data analysis techniques used are multiple linear regression analysis and the classical assumption test, which are processed using the Views 12 program. The results of this study indicate that the nature of industry has no positive but significant effect on financial statement fraud, the financial target variable has no effect and is insignificant to financial statement fraud, and the financial stability variable has a positive and significant effect on financial statement fraud. And simultaneous testing shows that the nature of the industry, financial targets, and financial stability have a positive and significant effect on fraudulent financial statements. The renewal in this research from previous research is in the sector and year used in the sample. And there is rarely research that uses variables like the nature of industry.